Realitas Dan Kontradiksi Regulasi Guru Honorer Tahun 2023 di Indonesia - Nurul amelia; Emma Yunika Puspasari (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2023)
This research intends to analyze student perceptions of the 2023 honorary teacher regulation in Indonesia and the motives behind their interest in becoming teachers towards the 2023 honorary teacher regulation in Indonesia. This research uses a qualitative approach with an intrinsic case study type of research. The subjects of this study were students of the economic education class of 2019, State University of Malang. The researcher chose this subject because based on preliminary studies and circulating issues related to the 2023 honorary teacher regulations in Indonesia that some 2019 economics education students are still interested in becoming teachers after the 2023 honorary teacher regulations in Indonesia. According to the results of interviews conducted with students of the economic education class of 2019 at the State University of Malang, there are five themes in student perceptions of the 2023 honorary teacher regulation in Indonesia, namely (1) Receiving stimuli or objects from outside the individual, (2) Knowledge related to the 2023 honorary teacher regulation , (3) Welfare for teachers and preparing professional teachers, (4) Evaluation of the 2023 honorary teacher regulation, (5) Suggestions for better changes. While the interviews were obtained on the motives behind the interest in becoming a teacher regarding the regulation of honorary teachers in 2023 in Indonesia, there are eight themes, namely (1) Having knowledge about the profession as a teacher, (2) Happy in the field as a teacher, (3) Interested in the profession as a teacher , (4) Attention to the profession as a teacher, (5) Having a desire to become a teacher, (6) Making efforts to become a teacher, (7) Confident in choosing a profession as a teacher, (8) Feeling comfortable with the teaching profession.